IMPROVING THE METHODOLOGY FOR ASSESSING THE TRAIN TRAFFIC SAFETY AT THE RAILWAY - Bulakh, M. O. (Science and Transport Progress, 2020)
Purpose. Despite the fact that the current methodology in Ukraine for assessing the train traffic safety at the railway does not provide a real and adequate picture, and foreign experience does not open up the possibility of a similar solution to the problems at Ukrainian railways, the goal has been set to improve the methodology for assessing the train traffic safety at the railway. Methodology.To improve the methodology for assessing the train traffic safety at the railway during a technical audit, the use of four indicators is proposed: the number of accidents for which losses are accrued; number of casualties; the number of traffic accidents that occurred during the year, but their consequences are not related to financial losses; number of violations identified by traffic safety auditors. Findings.The author has improved the methodology for assessing the train traffic safety at the railway. At the same time, four indicators were introduced in the methodology to calculate the train traffic safety at the railway. The ranking of these indicators was also performed. Using statistical data on the adopted indicators, a mathematical model was obtained for the integral assessment of train safety, on the basis of which a comparative assessment of traffic safety was performed at Ukrzaliznytsia JSC. As a result, it should be noted that the dynamics of the state of traffic safety in 2015-2018 has a different picture compared to the usual number of traffic accidents in Ukrzaliznytsia JSC. An improved methodology for assessing the state of train traffic safety at the railway allows us to perform adequate calculations and establish the real state of traffic safety during a technical audit. Originality. The author has improved the methodology for assessing the train traffic safety at the railway, which can be applied during the technical audit. Practical value. The improved methodology makes it possible to assess the general level of train traffic safety and establish real threats and risks in the process of technical audit, which, in the future, can be eliminated when developing appropriate measures and actions.